Emerging infectious diseases in an island ecosystem: the New Zealand perspective. - Crump, J A (Centers for Disease Control and Prevention, 2001)
Several unique features characterize infectious disease epidemiology in New Zealand. Historically, well-organized, government-run control programs have eliminated several zoonoses. More recently, however, communicable disease control has been mixed. Rates of rheumatic fever, tuberculosis, and enteric infectious are high, and rates of meningococcal disease are increasing. These diseases are over-represented in New Zealanders of Polynesian descent, who generally live in more deprived and overcrowded conditions than do those of European descent. Measles and pertussis epidemics are recurring because of inadequate vaccine coverage, despite a well-developed childhood immunization program. A progressive response to the HIV epidemic has resulted in relatively low rates of infection, particularly among injecting drug users; however, the response to other sexually transmitted infections has been poor. A key challenge for the future is to build on successful strategies and apply them to persisting and emerging infectious disease threats in a small, geographically isolated country with limited economic resources.